2015
DOI: 10.1093/infdis/jiv555
|View full text |Cite
|
Sign up to set email alerts
|

Measles Virus Neutralizing Antibody Response, Cell-Mediated Immunity, and Immunoglobulin G Antibody Avidity Before and After Receipt of a Third Dose of Measles, Mumps, and Rubella Vaccine in Young Adults

Abstract: Background Two doses of measles-mumps-rubella (MMR) vaccine are 97% effective against measles, but waning antibody immunity and two-dose vaccine failures occur. We administered a third MMR dose (MMR3) to young adults and assessed immunogenicity over 1 year. Methods Measles virus (MeV) neutralizing antibody concentrations, cell-mediated immunity (CMI), and IgG antibody avidity were assessed at baseline, 1-month, and 1-year after MMR3. Results Of 662 subjects at baseline, 1 (0.2%) was seronegative (<8 mIU/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
(31 reference statements)
2
30
1
1
Order By: Relevance
“…Although MMR vaccine is very efficacious to induce a protective response against measles, considering that a physiological decline of the humoral response has been revealed in some studies [35], it could be important to monitor the population 10-15 years after vaccination, in order to revaccinate the seronegatives. However, since booster revaccination might not induce a sustainable increase of MV antibodies [40], it could be advisable to implement the prophylaxis with alternative vaccines that could obviate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Although MMR vaccine is very efficacious to induce a protective response against measles, considering that a physiological decline of the humoral response has been revealed in some studies [35], it could be important to monitor the population 10-15 years after vaccination, in order to revaccinate the seronegatives. However, since booster revaccination might not induce a sustainable increase of MV antibodies [40], it could be advisable to implement the prophylaxis with alternative vaccines that could obviate this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The study population and exclusion criteria have been previously described in detail [17, 22]. Briefly, the study population included healthy young adults aged 18–28 years who received care from the Marshfield Clinic (Marshfield, WI) or who participated in a longitudinal study examining immune response to a second dose of MMR vaccine at Marshfield Clinic.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Paunio et al [86] reported during the 1988-89 measles outbreak in Finland that once and twice-vaccinated individuals had a crude relative risk of infection of 15.6 and 2.3, respectively, compared with thrice vaccinated individuals. Recently, minimal qualitative improvements in measles immune response magnitude and duration after a third MMR dose were reported in healthy young adults in the United Sates [140]. However, plaque reduction neutralization testing was performed using Edmonston measles virus, so it was not assessed if a third dose could re-boost the polyclonal immune response and clinical efficacy against the circulating genotypes.…”
Section: Strategy Proposal and Key Messagesmentioning
confidence: 99%